Application of Problem-Based Learning Model (PBL) as an Effort to Overcome Misconceptions in Black Body Radiation Material - Thufail Mujaddid Al-Qoyyim (Balai Publikasi Indonesia, 2023)
Physics cannot be separated from things that are conceptual. The concept of physics is a description or definition of the physical variables that exist in events in the universe. It's just that, often there is a problem in students' understanding of concepts where there is a discrepancy between the definitions that are understood and those conveyed by experts. This problem is called a misconception. Misconceptions can occur because the concepts that students understand through observation of everyday events are different from the theories obtained in the learning process in class, one of which is on black body radiation material. One learning model that can overcome misconceptions is a problem-based learning model or Problem Based Learning (PBL). The purpose of this study was to reduce misconceptions about black body radiation and to determine the effectiveness of PBL in overcoming misconceptions about black body radiation. This research is a type of experimental research using a pre-experimental design pre-test post-test group. The results showed that PBL can reduce misconceptions and is quite effective as an effort to reduce misconceptions about black body radiation material marked with an N-Gain value of 0.55.